Exploring Consent to Use Real-World Data in Lung Cancer Radiotherapy: Decision of a Citizens' Jury for an 'Informed Opt-Out' Approach. - Kapadi, Arbaz; Turner-Uaandja, Hannah; Holley, Rebecca; Wicks, Kate; Hamrang, Leila; Turner, Brian; van Staa, Tjeerd; Bowden, Catherine; Keane, Annie; Price, Gareth; Faivre-Finn, Corinne; French, David; et al. (Health Care Analysis, 2025)
An emerging approach to complement randomised controlled trial (RCT) data in the development of radiotherapy treatments is to use routinely collected 'real-world' data (RWD). RWD is the data collected as standard-of-care about all patients during their usual cancer care pathway. Given the nature of this data, important questions remain about the permissibility and acceptability of using RWD in routine practice. We involved and engaged with patients, carers and the public in a two-day citizens' jury to understand their views and obtain decisions regarding two key issues: (1) preferred approaches to consent for the use of RWD within the context of patients receiving radiotherapy for lung cancer in RAPID-RT and (2) how RWD use should be best communicated to patients. Individual views were polled using questionnaires at various stages of the jury, whilst group discussion activities prompted further dialogue about the rationale behind choices of consent. Key decisions obtained from the jury include: (1) an opt-out approach to consent for the use of RWD; (2) the opt-out approach to consent should be informed. Furthermore, it was advised that information and communication regarding the consent process and use of RWD should be accessible, clear and available in a variety of formats. It is important that the consent process for patient data use is underpinned by principles of autonomy and transparency with clear channels of communication between those asking for and giving consent. Moreover, the process of seeking consent from patients should be proportionate to the risks presented from their participation.